Islamic Religious Education Curriculum and Strengthening Religious Moderation in Indonesia - Diwani Elfarisyah; Juliani; Dewi Agustin; Imelda Ariska; Sintia (Journal of Contemporary Gender and Child Studies, 2024)
This study seeks to examine the role of the Islamic Religious Education curriculum in enhancing religious moderation in Indonesia. Religious moderation is a crucial factor in fostering harmony within community life amid the variety of ethnicities, religions, and cultures. The PAI curriculum possesses significant potential in promoting the values of religious moderation that emphasize tolerance, anti-radicalism, and appreciation for differences. This study employs a qualitative approach using a literature study method. Data were collected from various sources including education policy documents, journal articles, and relevant books. The analysis focused on identifying the concept of diverse moderation in the PAI curriculum and its application in the context of formal education in Indonesia. The findings indicate that the PAI curriculum has incorporated the values of religious moderation through moral education, inclusive religious perspectives, and the cultivation of a tolerant attitude. However, implementation on the ground continues to encounter challenges, such as inconsistent understanding among educators and the absence of specialized training on diverse moderation. Additionally, open materials that integrate the values of diverse moderation require enhancement to be more pertinent to the challenges posed by globalization and digitalization. In summary, the PAI curriculum plays a pivotal role in reinforcing religious moderation in Indonesia. Nonetheless, its effectiveness is largely contingent upon the alignment of policies, real-world implementation, and the enhancement of educators' competencies. Consequently, collaborative efforts are essential among the government, educational institutions, and the community to ensure that the values of religious moderation are effectively ingrained through the Islamic Religious Education curriculum.